2013
DOI: 10.1371/journal.pone.0067612
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PIMA™® Point of Care Technology for CD4 T Cell Enumeration in Kenya

Abstract: CD4+ T cell enumeration is used to determine eligibility for antiretroviral therapy (ART) and to monitor the immune status of HIV-positive patients; however, many patients do not have access to this essential diagnostic test. Introducing point of care (POC) testing may improve access. We have evaluated Alere’s PIMA™, one such POC device, against conventional CD4+ testing platforms to determine its performance and validity for use in Kenya. In our hands, Alere PIMA™ had a coefficient of variability of 10.3% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 23 publications
10
28
0
Order By: Relevance
“…This is in line with the results of previous studies that showed excellent instrumental precision with mean %CV of <5% reflecting the significant contribution of operators to the %CV 20,22. The Pima CD4 results using venous blood showed acceptable correlation and agreement with the FACSCalibur results, similar to those reported by previous studies2023,26,46 and partially in agreement with the study by Mwau et al47 in Kenya, comparing Pima CD4 with FACSCount. Mwau et al47 obtained discordant results comparing Pima CD4 with FACSCalibur but concordant results comparing Pima CD4 with FACSCount.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in line with the results of previous studies that showed excellent instrumental precision with mean %CV of <5% reflecting the significant contribution of operators to the %CV 20,22. The Pima CD4 results using venous blood showed acceptable correlation and agreement with the FACSCalibur results, similar to those reported by previous studies2023,26,46 and partially in agreement with the study by Mwau et al47 in Kenya, comparing Pima CD4 with FACSCount. Mwau et al47 obtained discordant results comparing Pima CD4 with FACSCalibur but concordant results comparing Pima CD4 with FACSCount.…”
Section: Discussionsupporting
confidence: 92%
“…The Pima CD4 results using venous blood showed acceptable correlation and agreement with the FACSCalibur results, similar to those reported by previous studies2023,26,46 and partially in agreement with the study by Mwau et al47 in Kenya, comparing Pima CD4 with FACSCount. Mwau et al47 obtained discordant results comparing Pima CD4 with FACSCalibur but concordant results comparing Pima CD4 with FACSCount. This discrepancy could be because of less reliable results generated by the FACSCalibur used, which showed a substantial absolute bias (LOA) against the FACSCount of −76.5 cells per microliter (−316 to 163).…”
Section: Discussionsupporting
confidence: 91%
“…For a count of 200 cells/mm 3 , 29 cells represents 14.5%. The precision of Pima CD4 was in line with the CV of 10.3% found in the study conducted in Kenya by Mwau and colleagues [34].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, a recent study in Kenya showed lower performance than our [34]. The influence of different operators (2 to 9 sites) [31] and the use of capillary blood to determine the sensibility and specificity may explain the lower performance of Pima CD4 when compared to FACSCount or when compared to CyFlow SL3 [34].…”
Section: Discussionmentioning
confidence: 58%
“…These POC have been dedicated to the clinical team, especially when the number of patients is not too high [10][11][12].…”
Section: Introductionmentioning
confidence: 99%